(untitled) (Abhat Journal, 2025)
This study aims to assess the efficiency of agricultural land use in the north of Kirkuk governorate based on the natural vegetation difference index (NDVI) and a set of accompanying environmental indicators, such as soil type, slope, altitude above sea level, and climate. The study area covers an estimated area of 3,282 km2, and includes various administrative units, namely al-Dibs, Al-ton bridge, sirkran, Shawan, and Qarah hangir, which represent different geomorphological and topographic environments. The results of the NDVI analysis showed a clear discrepancy in the density of vegetation, where the highest concentration was recorded in the areas of molasses and sarkran, due to the availability of Steppe soils (Xk26-2/3a and yy10-2ab) and moderate slope, while the lowest values appeared in Qarah hangir due to the rugged terrain and its extreme altitude (660–1200m). The study also revealed a direct relationship between vegetation cover and the efficiency of land use for wheat cultivation, as high NDVI values were associated with the height of cultivated areas, especially in molasses and Walton Bridge. On the other hand, the soil analysis showed that type Xk28-b is the most suitable for agriculture, covering more than 40% of the area. While the soils Yy10-2ab and VC1-3a represent an agricultural challenge due to poor drainage or their mountainous nature. Climatic factors, especially the distribution of precipitation and temperatures, also contributed to determining the ideal period for planting between November and April. The study found that the integration of NDVI data with environmental characteristics provides accurate insight to guide plans for the optimal use of agricultural land, and enhances the opportunities for sustainable agricultural reclamation in the region, especially if agriculture is adapted to the nature of the soil, terrain and climate.